Reducing length of antibiotics for children with ear infections: protocol for a cluster-randomized trial in the USA - Amy Keith; Timothy C Jenkins; Sonja O'Leary; Amy B Stein; Sophie E Katz; Jason Newland; Deborah J Rinehart; Aiden Gilbert; Sherry Dodd; Cindy M Terrill; Holly M Frost (Becaris Publishing Limited, 2023)
Aim: Preventing unnecessarily long durations of antibiotic therapy is a key opportunity to reduce antibiotic overuse in children 2 years of age and older with acute otitis media (AOM). Pragmatic interventions to reduce durations of therapy that can be effectively scaled and sustained are urgently needed. This study aims to fill this gap by evaluating the effectiveness and implementation outcomes of two low-cost interventions of differing intensities to increase guideline-concordant antibiotic durations in childrenwith AOM. Methods: The higher intensity intervention will consist of clinician education regarding guidelinerecommended short durations of antibiotic therapy; electronic health record (EHR) prescription field changes to promote prescribing of recommended short durations; and individualized clinician audit and feedback on adherence to recommended short durations of therapy in comparison to peers, while the lower intensity intervention will consist only of clinician education and EHR changes. We will explore the differences in implementation effectiveness by patient population served, clinician type, clinical setting and organization as well as intervention type. The fidelity, feasibility, acceptability and perceived appropriateness of the interventions among different clinician types, patient populations, clinical settings and intervention type will be compared. We will also conduct formative qualitative interviews with clinicians and administrators and focus groups with parents of patients to further inform the interventions and study. The formative evaluation will take place over 1.5 years, the interventions will be implemented over 2 years and evaluation of the interventions will take place over 1.5 years. Discussion: The results of this study will provide a framework for other healthcare systems to address the widespread problem of excessive durations of therapy for AOM and inform national antibiotic stewardship policy development.